PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, FIRM SIZE, DAN EARNING PE SHARE TERHADAP DIVIDEND PAYOUT RATIO (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Muammar Hanif; Bustamam Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The objective of this research is to examine the effect of debt to equity ratio, return on asset, firm size, and earnings per share on dividend payout ratio either simultaneosly or partially toward dividend payout ratio. The samples are manufacture companies listed on the Indonesia Stock Exchange during five years (2011-2015). The sample selection is done by using purposive sampling method. Secondary data are proceed by using balanced panel data. Total samples are 18 companies with a total of 90 observations. Mulitiple linear regression is used to annalyze the data of this study.The results show that (1) the simultaneous of debt to equity ratio, return on asset, firm size, and earnings per sharehave effect on dividend payout ratio. (2) Partially, debt to equity ratioand firm size do not have influence toward dividend payout ratio, whereas return on asset andearning per share have positive influence toward dividend payout ratio. Keywords: Dividend payout ratio, debt to equity ratio, return on asset, firm size, and earnings per share.